Evaluation of Cereals and Pseudocereals Suitability for the Development of New Probiotic Foods - Monika Kocková; Monika Dilongová; Eva Hybenová; L’ubomír Valík (Journal of Chemistry)
The aim of the present work was to evaluate suitability of cereals and pseudocereals for the development of new probiotic foods and to evaluate the stability of cereal and pseudocereal porridges fermented by probiotic strain Lactobacillus rhamnosus GG. Ten samples of cereals and pseudocereals obtained from Slovak mill house and markets were used in this work. A mixture of each cereal and pseudocereal samples with water (10% w/v) was inoculated after sterilization with coequal number of Lactobacillus rhamnosus GG, to obtain approximately 5-6 log colony form units per gram of suspensions. Fermentation was led at 37°C during 10 hours. Fermented suspensions were stored for 21 days at 5°C. Monitoring of cell counts, pH value, and concentration of organic acids during fermentation and storage was done.